Analisis Motivasi Kerja Dan Pemberian Insentif Terhadap Kinerja Tenaga Kesehatan Dimasa Pandemi Covid-19 (Studi Kasus Di Rs Toeloengredjo Pare Kediri) - Karjito Karjito; Deby Santyo Rusandy (Universitas Islam Kadiri, 2022)
This study aims to determine the effect of work motivation, providing incentives on the performance of paramedics during the covid 19 pandemic. The research method was carried out by conducting surveys and with a quantitative approach. Data collection was done by distributing questionnaires to 75 respondents. Data analysis techniques were carried out through SPSS version 22.0 including regression analysis, coefficient of determination test, f test and hypothesis testing. The results of data analysis obtained the value of the coefficient of determination (R2) which was determined by R square of 0.502 (squaring of the correlation coefficient or R, ie 0.709 x 0.709 = 0.502) or equal to 50.2%, this value indicates that the relationship of the independent variable motivation, incentives with a performance dependent variable of 50.2%. While the rest (100% - 50.2% = 49.8%) is influenced by external variables. The results of the F test showed that the Fcount value was 36.301 with a significance level of 0.000 and for Fcount > Ftable (36.301 > 3.120) and the significance level was 0.000 <0.05. This shows that H0 is rejected and Ha is accepted, which means that the independent variable (free) namely Motivation and Incentives simultaneously or jointly has a positive and significant effect on the dependent variable (bound), namely Performance. Based on the results of hypothesis testing, it was found that the motivational variable had a significance value of 0.000 < 0.050. Meanwhile, the t-count value for motivation is 5.590, which is greater than the t-table, which is 1.993. So it can be concluded that H0 is rejected and Ha is accepted. This means that there is an influence of motivation on performance, while the incentive variable has a significance value of 0.804 > 0.050. Meanwhile, the value of t-count Incentive is 0.249, which is smaller than the t-table, which is 1.993. So it can be concluded that H0 is accepted and Ha is rejected. This means that there is no effect of incentives on performance.